PERAN PENYULUHAN TERHADAP KELOMPOK PETANI PADI DI DESA NAGARI SARILAMAK KECAMATAN HARAU KABUPATEN LIMA PULUH KOTA - Bukhori, Imam '; ', Rosnita '; ', Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Counseling is a non-school education system in which adults and youth learn by doing. Counseling is a partnership between government, landowners and communities, providing care and education planned to find the needs of the community. The ultimate goal is the advancement of society. Rice is a political commodity that is very strategic because it is a staple food for more than 95 percent of Indonesia's population, rice farming is a provider of employment and as a source of income for about 21 million farming households and the benchmark of food availability for Indonesian. Tujuan research is to determine the role of extension workers to farmers in the sub-district Sarilamak Nagari Harau City District Fifty? And to determine the factors supporting and inhibiting factors to the agents in carrying out counseling in the village of Nagari Harau Sarilamak District of Kota District Fifty? The method used is survey method with a sample of 93 farmers. The role of extension to a group of rice farmers in a category is, extension means quite a role to a group of rice farmers in the village of Nagari Harau Sarilamak Subdistrict District Fifty State. Supporting factor for the extension in implementing counseling in the village of Nagari Harau Sarilamak District of Kota District Fifty is the use of seed / fertilizer quality seeds, and Supply / Water Management. While the inhibiting factors to the agents in carrying out the repair counseling is how to do farming, control of pests of plants, Treatment Harvest and Post Harvest and Marketing. Keywords: Role of Extension, Rice Farmer